THE MANAGEMENT OF HIV INFECTION IN PREGNANCY - Valerian, Clara Marcaelia; Kemara, Ketut Putera; Megadhana, I Wayan (E-Jurnal Medika Udayana, 2013)
The Human Immunodeficiency Virus (HIV) is a RNA retrovirus which causes the clinical disease termed the acquired immunodeficiency syndrome (AIDS). Mother-to-child transmission is the main source of spreading HIV infection to the child with frequency is as high as 25-30%. This may occurred because of the intrapartum maternal blood exposure, infected genital tract secretions and during breastfeeding. The right combination of ARV treatment and elective section caesarean delivery has been proved to reduce the mother-to-child transmission of HIV infection prevalence and preventing obstetric complications significantly. Consultation and follow up with specialists is highly recommended.
Keywords: HIV, pregnancy